2018
DOI: 10.1002/mbo3.708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fiber levels on bacterial composition with age in the cecum of meat rabbits

Abstract: This study investigated the influence of dietary fiber levels on the growth performance, digestion, metabolism, and cecal microbial community of rabbits with different diets at different age. The different levels of dietary natural detergent fiber (NDF) were formulated accordingly: 400(A), 350(B), 300(C), 250(D) g/kg original matter basis, respectively; the different ages were 52, 62, and 72 days. With NDF increasing, the average daily feed intake (ADFI) and feed conversion rate (FCR) were increased, whereas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
1
10
0
2
Order By: Relevance
“…The relative abundances of the main phyla did not differ between both rabbit breeds, except for the phylum Verrucomicrobia, which showed a higher abundance in Elco rabbits (Additional file 2 : Table S2). This could be explained by the presence of the phyla Firmicutes, Bacteroidetes, and Proteobacteria as they are significantly affected by diet factors (e.g., dietary fibre type and level) [ 20 , 21 ] and our rabbits were reared under identical conditions, receiving the same diet. Similarly, Li et al found that individuals of the same horse breed raised under different feeding regimes showed tremendous variations in the relative abundances of Firmicutes and Bacteroidetes but not in those of Verrucomicrobia [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundances of the main phyla did not differ between both rabbit breeds, except for the phylum Verrucomicrobia, which showed a higher abundance in Elco rabbits (Additional file 2 : Table S2). This could be explained by the presence of the phyla Firmicutes, Bacteroidetes, and Proteobacteria as they are significantly affected by diet factors (e.g., dietary fibre type and level) [ 20 , 21 ] and our rabbits were reared under identical conditions, receiving the same diet. Similarly, Li et al found that individuals of the same horse breed raised under different feeding regimes showed tremendous variations in the relative abundances of Firmicutes and Bacteroidetes but not in those of Verrucomicrobia [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Saki et al (2012) reported that feeding organic acid mixture resulted in the decreased cecal relative weight of broilers. Considering the positive relationship between the fiber content of diets and cecal relative weight (Wu et al, 2019), the decrease in cecal weight in the experimental chickens treated with fermented filtrate may be attributed to the improved fiber digestion in the upper part of the digestive tract and hence less fiber reaching the caeca of broilers. In support to our inference, Rodjan et al (2018) reported that dietary administration of organic acids and probiotics increased the ability of broilers to degrade crude fiber.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in other animals, the fecal microbiota of wild and domesticated individuals within the same species are different, and their fecal microbiota is affected by feed differences [20]. Moreover, low-fiber diets or high-protein diets can alter the diversity of gut microbiota and may cause adverse effects, such as diarrhea and reduced fertility due to obesity [40,41]. Thus, in future studies, it is crucial to assess how much feed characteristics affect the gut microbiota of domesticated grasscutters.…”
Section: Discussionmentioning
confidence: 99%